2007
DOI: 10.1016/j.jembe.2007.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Brown Ring Disease on the energy budget of the Manila clam Ruditapes philippinarum

Abstract: Brown Ring Disease (BRD) is a bacterial disease caused by the pathogen, Vibrio tapetis. The disease induces formation of a brown deposit on inner shell of the Manila clam, Ruditapes philippinarum. Development of this disease is correlated with a decrease in the condition index of infected clams. Experiments were conduced in order to assess the effect of the development of BRD on two parameters affecting the energy balance of the clams: the clearance and the respiration rates. Experiments were performed in a ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
32
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 49 publications
8
32
0
1
Order By: Relevance
“…Activity of HK in labial palps of oysters varies with feeding ration (Bacca 2007, p. 123). Therefore, the reduction in HK activity observed in infected oysters may reflect a decrease in feeding activity, which is symptomatic of pathogen infection in bivalves (Flye-Sainte-Marie et al 2007, Genard et al 2011.…”
Section: Relationships Between Oyster Mortalities Pathogens and Enermentioning
confidence: 99%
“…Activity of HK in labial palps of oysters varies with feeding ration (Bacca 2007, p. 123). Therefore, the reduction in HK activity observed in infected oysters may reflect a decrease in feeding activity, which is symptomatic of pathogen infection in bivalves (Flye-Sainte-Marie et al 2007, Genard et al 2011.…”
Section: Relationships Between Oyster Mortalities Pathogens and Enermentioning
confidence: 99%
“…Indeed, several studies on marine invertebrates have shown that respiration rate and CS activity were positively correlated (Moran and Manahan 2004;Meyer et al 2007). In juvenile Manila clams, respiration rate decreased with the development of brown ring disease symptoms (Flye-Sainte- Marie et al 2007). These authors observed that the oxygen consumption decrease was correlated with decreased feeding (clearance rate) and could be interpreted as a compensatory reduction of metabolic rate, as was observed by Widdows and Hawkins (1989).…”
Section: Characterization Of the Massive Mortalitymentioning
confidence: 99%
“…and can affect both Ruditapes decussatus and R. philippinarum (see Villalba et al, 2004, for a review). Both pathologies can interfere with host energy balance (Ngo and Choi, 2004;Park et al, 2006;Leite et al, 2004;Flye-Sainte-Marie et al, 2007b) and can be responsible for mass mortalities (see e.g. Paillard et al, 1989;Castro et al, 1992;Paillard, 1992Paillard, , 2004bVillalba et al, 2005Villalba et al, , 2004.…”
Section: Introductionmentioning
confidence: 99%